Electrostatically assembled core-shell particles and their reaction sintering for SiC membranes with improved oil/water separation and thermal regeneration efficiency - Junyou Li; Qilin Gu; Huiqin Zhang; Zhaoxiang Zhong; Yiqun Fan; Weihong Xing (Advanced Membranes)
Porous SiC membranes prepared through the reaction sintering between the additive and surface oxidation generated silica have gained increasing attention in the fields of oil-water separation. Previous efforts mainly focused on the types and contents of additives incorporated by physically mixing process, while their distribution on the microstructure and separation performance of SiC membranes has been rarely involved. This work proposed to prepare SiC membranes by uniformly coating AlOOH sol on SiC particles via the electrostatic interaction and the subsequent reaction sintering of the derived SiC@alumina core-shell particles. It is found that the surface coating enabled the homogeneous dispersion of the additives in SiC powder matrix, which not only facilitated the reactive sintering process and notably reduced the amount of residual SiO2 in SiC membranes, but also homogenized the pore structure. Also, the oxidation pathway of SiC had been altered, which substantially retarded the oxidation degree. Impressively, the as-prepared SiC membranes exhibited 20 ​% improvement in alkali resistance, and enhanced oil-in-water emulsion separation efficiency when compared with those prepared by the conventional mechanical mixing method. Besides, the fouled SiC membranes prepared from the core-shell units can be more efficiently regenerated by using the emerging Joule heating technique. The present work provides a facile and effective pathway to the preparation of high-performance SiC membranes through the reaction sintering of rationally designed core-shell particles for high-efficient separation.